Application of a novel rectangular filtering microfluidic device for microfilarial detection - Asawakarn, Sariya; Pimpin, Alongkorn; Jeamsaksiri, Wutthinan; Sripumkhai, Witsaroot; Jitsamai, Wanarit; Taweethavonsawat, Piyanan; Piyaviriyakul, Prapruddee (Frontiers in Veterinary Science, 2023)
The rectangular filtering microfluidic chip was invented using microfluidics device fabrication technology and can separate living microfilariae from blood samples without a syringe pump. The diagnostic results are highly effective. The device is based on the principle of separating millions of blood cells from microfilariae using a rectangular filter structure. It disperses fluid evenly into the flow-passage channel, and its rectangular filter structure is the key to success in reducing the pressure and separating blood cells from microfilariae effectively. The flow rate and blood cell concentration were optimized in our study. The chip is intended to be a point-of-care device that can reduce the use of superfluous instrumentation in the field. The technology is designed to be rapid, accurate, and easy-to-use for all users, especially those in remote areas.